Efficacy of PBTZ169 and pretomanid against Mycobacterium avium, Mycobacterium abscessus, Mycobacterium chelonae, and Mycobacterium fortuitum in BALB/c mice models - Zheng, Luyao; Qi, Xueting; Zhang, Weiyan; Wang, Hong; Fu, Lei; Wang, Bin; Chen, Xi; Chen, Xiaoyou; Lu, Yu (Frontiers in Cellular and Infection Microbiology, 2023)
Objectives We aimed to evaluate the activity of PBTZ169 and pretomanid against non-tuberculous mycobacteriosis (NTM) in vitro and in vivo. Methods The minimum inhibitory concentrations (MICs) of 11 antibiotics, against slow-growing mycobacteria (SGMs) and rapid-growing mycobacteria (RGMs) were tested using the microplate alamarBlue assay. The in vivo activities of bedaquiline, clofazimine, moxifloxacin, rifabutin, PBTZ169 and pretomanid against four common NTMs were assessed in murine models. Results PBTZ169 and pretomanid had MICs of >32 μg/mL against most NTM reference and clinical strains. However, PBTZ169 was bactericidal against Mycobacterium abscessus (3.33 and 1.49 log10 CFU reductions in the lungs and spleen, respectively) and Mycobacterium chelonae (2.29 and 2.24 CFU reductions in the lungs and spleen, respectively) in mice, and bacteriostatic against Mycobacterium avium and Mycobacterium fortuitum. Pretomanid dramatically decreased the CFU counts of M. abscessus (3.12 and 2.30 log10 CFU reductions in the lungs and spleen, respectively), whereas it showed moderate inhibition of M. chelonae and M. fortuitum. Bedaquiline, clofazimine, and moxifloxacin showed good activities against four NTMs in vitro and in vivo. Rifabutin did not inhibit M. avium and M. abscessus in mice. Conclusion PBTZ169 appears to be a candidate for treating four common NTM infections. Pretomanid was more active against M. abscessus, M. chelonae and M. fortuitum than against M. avium.